Emotional design for digital games for learning: The effect of expression, color, shape, and dimensionality on the affective quality of game characters. (December 2020) - Plass, Jan L.; Homer, Bruce D.; MacNamara, Andrew; Ober, Teresa; Rose, Maya C.; Pawar, Shashank; Hovey, Chris M.; Olsen, Alvaro
Abstract: What is the affective quality of specific design features of game characters? The Integrative Model of Emotion in Game-based Learning (EmoGBL) describes common mechanisms of how emotion and learning processes interact to foster specific learning outcomes. In the present paper, we asked how color, shape, expression, and dimensionality of game characters induce emotions in digital games for learning. We investigated learners' perception of the affective quality of these four different visual design features for adults and adolescents using a forced choice paradigm (studies 1–3), as well as the PANAS-X and qualitative measures (study 4). Participants were shown a series of game characters and were asked to report their emotional response. Results show the relative contribution of the four visual attributes on players' perception of affective quality, with the visual design features of expression and dimensionality having the strongest effect, color a medium-sized effect, and shape a small to medium-sized effect. Highlights: The affective quality of design features of characters for learning games was investigated. Immersion (Immersive 3D vs. Desktop 2D) had a large effect on affective arousal. Expression (sad v. neutral v. happy) had a large effect on affective arousal. Color (cold v. warm) had a medium-sized effect on affective arousal. Shape (square v. round) had a small to medium-sized effect on affective arousal.